Overview of Anxiety in the Elderly at UPT Tresna Werdha Batoro Katong Ponorogo Services - Endri, Risye; Monica Ranti Hansari (Journal for Quality in Public Health, 2022)
The total population of more than 60 years which continues to increase makes Indonesia enter the era of “aging population”. Increasing the number of elderly population can be a public health challenge that requires serious treatment because naturally the elderly experience a decrease both in terms of physical, biological, and psychological. Elderly shows a variety of psychological problems. The goal of the research is to study the picture of the elderly at The Social Services Unit of Tresna Werdha Batoro Katong Ponorogo. The research design uses qualitative descriptive with cross sectional study research design.. The population is 62 respondents. The sampling technique is total sampling. The independent variable is a anxiety. The results showed that the elderly experienced anxiety from the level of not experiencing anxiety 18 respondent (29%), mild anxiety 20 respondents (32%), and moderate anxiety 24 respondents (39%). Symptoms of mild anxiety are tense, lethargic, can not sleep, wake up with lethargy, loss of interest, abdominal pain, and bloating. Symptoms of moderate anxiety are feeling tense, restlessness, difficulty going to sleep, waking up at night, waking up listlessly, loss of interest, reduced hobbies, muscle aches, palpitations, stomach twists, bloating, and nausea. Based on the results of research that anxiety is often experienced by the elderly. This is caused by distress, cognitive impairment, comorbid social factors, medical (pain an number of medical conditions), psychiatric (depression).